P060 The protective effect of necrosis inhibition on acute murine colitis induced by dextran sulphate sodium. (25th January 2019) - Kim, D; Koo, J S; Park, J H; Hwang, S H; Lee, D; Choe, J W; Hyun, J J; Jung, S W; Jeen, Y T; Lee, S W
Abstract: Background: Inflammatory bowel diseases (IBD) were characterised by uncontrolled chronic inflammation, which lead to cell death and organ damage. Although necrosis is thought to be a main cell death mechanism of IBD, few attempts have been made to reduce necrosis in IBD. The aim of this study investigated the effect of necrosis inhibition using a novel necrosis inhibitor (NI, NecroX-7) in acute murine colitis model and in vitro study. Methods: In order to confirm the necrosis inhibition effect of NI, intestinal epithelial cell line (IEC-18, rat) was used to analyse Cleaved PARP-1 fragment with western blot assay. And acute dextran-sodium sulphate (DSS)-induced colitis was generated in C57BL/6 mice. NI (30 mg/kg) was administered once a day via oral gavage for 8 days from the day before DSS administration. The severity of colitis was assessed by weight, colon length, and histological score, and HMGB1 immunochemistry was performed on harvested colon tissues to evaluate necrotic cell death qualitatively. The inflammatory cytokines mRNA expressions were measured by quantitative RT-PCR. Results: The expression of cleaved PARP-1 (55 kDa, necrosis marker) was reduced in the NI group, compared with the control group, whereas the cleaved PARP-1 fragment (89 kDa, apoptosis marker) was not different between two groups. In vivo study, NI treatment significantly reduced colitis represented by colon length (DSS + NI group 68.0 ± 4.7 mm vs. DSS group 62.6 ± 3.8 mm, p = 0.048) and histological score (DSS + NI group 11.4 ± 1.6 vs. DSS group 7.9 ± 1.3, p = 0.043). The immunohistochemical staining of HMGB-1 revealed that NI also reduced HMBG-1 expression significantly. In addition, the expression of inflammatory cytokines such as IL-1β, IL-12, MCP-1, TNF-α was reduced in NI group, especially IL-1β was significantly different between two groups ( p = 0.011). Conclusions: A necrosis inhibition effectively reduced DSS-induced colitis and inflammatory cytokines. Necrosis inhibition might be a new approach to treat inflammatory bowel disease.